Analysis of Digital Application Use in Dairy Cattle Production Management - Zubaidi Ilham; Franck Morais de Oliveira (Journal of Animal Husbandry, 2026)
Digital technology adoption in livestock farming has increased significantly over the last decade. Dairy cattle production management now integrates digital applications such as herd management software, precision monitoring systems, and mobile applications. These technologies enable real time monitoring of animal health, feeding behavior, and production performance. However, the extent of digital application utilization and its management implications still require comprehensive analysis. This study aims to analyze the role and effectiveness of digital applications in dairy cattle production management based on recent scientific literature. The research uses a qualitative literature review approach by examining 30 scientific publications related to digital technology adoption in dairy farming. Data were analyzed using thematic synthesis to identify major technological trends, management benefits, and adoption challenges. The results show that digital applications significantly improve management efficiency through automated monitoring, data based decision making, and improved animal health surveillance. Studies also report improvements in productivity, cost efficiency, and environmental performance. Despite these benefits, adoption barriers remain, including investment costs, data security concerns, and limited digital skills among farmers. The study concludes that digital applications play a strategic role in modern dairy cattle production management, particularly in supporting precision livestock farming systems. Future research should focus on integrating artificial intelligence and Internet of Things technologies to enhance decision support systems in dairy farming.